How to Deal with Menstrual Problems? - Ermiati E; Neneng R Puspitasari; Restuning Widiasih; Geuis A Mulyasari (Journal of Nursing Care, 2019)
Menstruation is the normal cycle experienced by all women’s, however it’s causes unstable emotions, irritable, crying, aggressive, provoking, pain, bleeding a lot of bleeding in a long duration. These problems would influence women’s well-being, so interventions are needed for women’s with menstrual problems. This systematic review aimed to describe the findings from studies about the interventions to deal with menstrual problems. The review process was conducted using electronic databases: PubMed, Proquest, Google scholar and EBSCO. The keywords used were Quality of life, Menstruation problems, Menstruation periods, Teenage, and Urban. The inclusion criteria of articles were taken from 2015 to 2018 while the exclusion criteria were articles that were non-English. The review identified a total of 12 articles. However, according to the inclusion and exclusion criteria, 5 articles were obtained. The method used was experimental and cross sectional study. In addition, the analysis was used content analysis process. Menstrual problems can be minimized by doing various physical exercises continuously and intensively, the factors of age and counseling from the closest person greatly determines the quality of life in adolescents with menstrual problems. In addition, providing TENS therapy and drug therapy among adolescent can help to improve the quality of life in adolescents with menstrual problems. Conclusions: Menstrual problems can be reduced in various ways, including physical, pharmacological and non-pharmacological treatments.